Monitoring of large and inconsistent deformation in coal mining area using point-like target offset tracking. Issue 4 (16th February 2022) - Liu, Zhenguo; Bian, Zhengfu; Liu, Wanli
ABSTRACT: Ground deformation in the coal mining area of Northwestern China is usually featured by large and inconsistent subsidence. Large subsidence brings great challenge to Differential Interferometric Synthetic Aperture Radar (DInSAR) and Permanent Scatterer Interferometry (PSI) technology due to the pixel-level offset in the range direction after co-registration, which could directly result in complete coherence loss even for the artificial Corner Reflectors (CRs). Offset tracking provides an alternative to capture the large deformation although the results could be biased due to the large deformation gradient and use of fixed correlation window size. In this paper, the point-like target (PT) offset tracking method is introduced to deformation monitoring in coal mining area with a levelly decreasing correlation window size. For each PT-centered SLC patch in the reference SAR image, the estimate from the larger correlation window will serve as a guide for the smaller one to locate the matching SLC patch in the slave SAR image, thus providing a guarantee that the residual offsets to be estimated remain to be a small fraction of the decreasing patch size. The offset estimates were evaluated by ground surveying results at 34 CRs obtained using single reference real-time kinematic (RTK) GPS technique, with a RMS error of 1/13-1/14 SLC pixel in both the range and azimuth directions.